Influence of voids on the flexural resistance of the NCF/RTM6 composites - Montoro, Sergio Roberto [UNESP]; Shiino, Marcos Yutaka [UNESP]; da Cruz, Tessie Gouvea [UNESP]; Hilario Cioffi, Maria Odila [UNESP]; Voorwald, Herman Jacobus Cornelis [UNESP] (Elsevier B.V., 2011)
A major difficulty to achieve maximum weight savings in the manufacture of composite structural components, is the tendency of these materials have the formation of voids and cracks in the interior and surface components. In aeronautical applications, controlling the volume fraction of fibers, resins and empty the components of composite is very hard. In this work, composites of epoxy matrix RTM6 reinforced with NCF (non crimp fabric carbon) processed by resin transfer molding (RTM) were characterized for porosity (P-ap) and density (rho(ad)). We used a method based on Archimedes' principle (ASTM C830) and the technique of helium pycnometer. The porosity values were compared with those determined by acid digestion (ASTM D3171). The mechanical properties of processed composites was evaluated by testing on the performing flexural and the results were correlated with the porosity value. All techniques tested to determine void content are satisfactory. The differents results can be justified for heterogeneous void distribution on laminate and differences among techniques characteristics. (C) 2011 Published by Elsevier Ltd. Selection and/or peer-review under responsibility of ICM11
Keywords: Composites; Flexural test; RTM; Voids